Cardiovascular side effects in patients treated with some selected antipsychotics. Preliminary results - Wierzbiński, Piotr; Zboralski, Krzysztof; Orzechowska, Agata; Florkowski, Antoni; Gałecki, Piotr (Current Problems of Psychiatry, 2011)
Introduction: Treatment with antipsychotics is associated with cardiovascular side effects. This results from mechanism of action of antipsychotic agents because these drugs are affinity antagonist at adrenergic histamine, cholinergic and serotonine receptors. Arrhythmias are the serious side effects. Treatment with antipsychotics may prolong QTc and increase the risk of dangerous supraventricular and ventricular arrhythmias.Objectives: The main aims of the research are the following: If any antipsychotics agents may prolong QT interval? If treatment with olanzapine, ziprasidone and aripiprazole may induce any arrhythmias? Methods: Data for this study were collected from 51 patients hospitalized in the Department of Adult Psychiatry and treated with olanzapine (n=20), aripiprazole (n =16), ziprasidone (n=15). All patients had 12 leads ECG two times: before admitting the drugs and during the treatment. All ECG were assessed on the presence of any abnormalities and QTc was calculated manually by using Bazzet formula.Results: Among treated patients no significant QTc prolongation was observed. There was no prolonged QTc over 450ms in Male and 470 ms in female patients treated with antipsychotics. Potassium level in all patients was within the norm. Bradykardia (< 50/min) and tachykardia (>100/min) was not observed among participants.Conclusions: Atypical antipsychotics such as olanzapine, aripiprazole, ziprasidone are cardiovascular safe drugs. They did not induce dangerous for life arrhythmias especially ventricular arrhythmia (known as torsades de pointes), which can progress to ventricular fibrillation and sudden death.